Pengujian bakteri endofit asal cabai dalam menekan pertumbuhan F. oxysporum f.sp. capsici penyebab penyakit layu fusarium pada cabai - Irma Handayani Sihombing; Mukhtar Iskandar Pinem; Irda Safni (Jurnal Agroekoteknologi, 2019)
ABSTRACTEndophytic bacteria are bacteria in plant tissues that do not cause disturbance in plants and can increase plant resistance to pests and pathogens as well increase plant growth. This study was aimed to determine the ability of endophytic bacteria isolated from chili plants in suppressing the development of fusarium wilt disease caused by F. oxysporum f.sp. capsici and utilize the capability of several carriers as a medium for growing endophytic bacteria to be stored, transported and applied. Endophytic bacteria are bacteria in plant tissues that do not cause disturbance in plants and can increase plant resistance to pests and pathogens and increase plant growth. This study was aimed to determine the ability of endophytic bacteria isolated from chili plants in suppressing the development of fusarium wilt disease caused by fungus F. oxysporum f.sp. capsici. The in vitro antagonistic test results showed that  the most effective endophytic bacteria againts isolate of  F. oxysporum f.sp. capsici was BE 12 isolate (20.41%). Isolate BE 12 which reacts positively to the fluorescence test has an effect in inhibiting the growth of mycelium from fungus F. oxysporum f.sp. capsici because the endophytic bacteria belong to P. fluorescens produces pyoluteorin and pyrrolnitrin compounds that are toxic to pathogen. The characteristic of morphology of all endophytic bacterial isolate a were circular colony with white colour,and flat elevation and undulate margin. Isolates of BE 2, BE 4 and BE 12 were Gram negative, while the other were Gram positive.